91-LGBT+ - Babin, Sylvette; Glenn, Clinton; Gayed, Andrew; Barbu, Adam; Williamson, Andrea; Varghese, Ricky; Flavelle, Genevieve (2017)
Dans la foulée du numéro précédent, qui portait sur les féminismes, ce dossier poursuit la réflexion sur la question des genres et des sexualités en s’attardant aux pratiques et aux théories qui cherchent à transcender la pensée binaire de la société patriarcale hétéronormative et cisnormative. On y explore notamment les stratégies déployées par les artistes afin de rendre visible les communautés LGBT+ et de faire entendre la multiplicité des voix en marge du régime patriarcal de production des savoirs.
Publisher: Presses de l'Université du Québec à Montréal
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; corps; cours; discipline; har4600; histoire de l'art; hétérosexisme; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; transféminisme

Otherwise: imagining queer feminist art histories - Jones, Amelia; Silver, Erin (Manchester University Press, 2016)
Otherwise: Imagining queer feminist art histories" is the first publication to address queer feminist politics, methods and theories in relation to the visual arts, including new media, installation and performance art. Despite the crucial contribution of considerations of 'queer' to feminism in other disciplines of the humanities, and the strong impact of feminist art history on queer visual theory, a visible and influential queer feminist art history has remained elusive. This book fills the gap by offering a range of essays by key North American and European scholars, both emerging and renowned, who address the historiographic and political questions arising from the relationship between art history and queer theory in order to help map exclusions and to offer models of a new queer feminist art historical or curatorial approach.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; europe; har4600; histoire de l'art; identités LGBTQIA2+; installation; performance; premier cycle; queer; régions géographiques; thématiques; transféminisme